Ultrastructural Studies on the Infundibulum of Oviduct in Emu (Dromaius novaehollandiae) - Naik, Raghu (Indian Journal of Veterinary Anatomy, 2019)
The ultrastructure of infundibulum was studied in eight adult apparently healthy emu birds. The mucosal surface contained spirally oriented unbranched longitudinal ridges in the funnel part of infundibulum with shallow furrows. The epithelial cells contained cylindrical cilia of uniform length and microvilli, in which clumps of cilia were observed. Four types of cells were observed in the lining epithelium, Viz., ciliated, non ciliated, basal and mucous secretary cells (Goblet cells). The goblet cell was distended with secretion and contained elongated mitochondria throughout the cytoplasm. The roots of cilia were found to be concentrated with prominentmitochondria. The columnar ciliated cells showed little evidence of secretary activity by membrane bound electron dense secretary granules.